2005
DOI: 10.1152/ajpgi.00256.2004
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2from Kupffer cells contributes to the hyperresponsiveness of hepatic portal circulation to endothelin-1 in endotoxemic rats

Abstract: We examined the role of thromboxane A2 (TXA2) in LPS-induced hyperresponsiveness of hepatic portal circulation to endothelins (ETs) and whether Kupffer cells are the primary source of TXA2 release in response to ET-1 in endotoxemia. After 6 h of LPS (1 mg/kg body wt ip) or saline (control), liver was isolated and perfused with recirculating Krebs-Henseleit bicarbonate buffer at a constant flow rate (100 ml.min(-1).kg body wt(-1)). ET-1 (10 pmol/min) was infused for 10 min. Portal pressure (PP) was continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 29 publications
7
49
0
1
Order By: Relevance
“…15,29,30 KCs are highly relevant for the production of vasoconstrictors in the intrahepatic microvasculature. 6,16 The effects observed in this study seem to be predominantly dependent on the KCs, because GdCl 3 pretreatment attenuated TLR4 and MyD88 expression after LPS pretreatment.…”
Section: Kc-dependent Effects Of Intraperitoneal Lpsmentioning
confidence: 73%
See 1 more Smart Citation
“…15,29,30 KCs are highly relevant for the production of vasoconstrictors in the intrahepatic microvasculature. 6,16 The effects observed in this study seem to be predominantly dependent on the KCs, because GdCl 3 pretreatment attenuated TLR4 and MyD88 expression after LPS pretreatment.…”
Section: Kc-dependent Effects Of Intraperitoneal Lpsmentioning
confidence: 73%
“…14,15 Therefore, KCs could have a leading role in the regulation of infection-related variceal bleeding, as proposed previously. 16 The activation of KCs is dependent on surface receptors such as Toll-like receptors (TLRs) and intracellular effectors such as MyD88.…”
mentioning
confidence: 99%
“…KCs form one week BLD and sham operated Male Sprague-Dawley rats weighing between 250-400 g were isolated as previously described (9,52). Cells were plated in 24-well plastic culture dishes (Corning, Corning, NY) at a concentration of 1 × 10 6 cells/well and cultured in 1000 l of RPMI 1640 medium (Sigma Chemical, St. Louis, MO) supplemented with 25 mM HEPES, 20% fetal bovine serum (FBS) and antibiotics (0.05% gentamycin sulfate).…”
Section: Kupffer Cell Isolation and Culturementioning
confidence: 99%
“…Thromboxane A 2 (TXA 2 ) is a potent cyclooxygenase (COX)-derived vasoconstrictor in the portal circulation and contributes to the overall vascular tone of the hepatic microcirculation (5)(6)(7). Our lab has shown that Kupffer cell (KC)-derived TXA 2 plays significant roles in the development of portal hypertension and hepatocellular injury in early fibrosis using the one-week bile duct ligation (BDL) model (8) and in mediating the hyperresponsiveness of the portal circulation to the vasoconstrictive effect of ET-1 during endotoxemia (9). In the same model, we have also shown that the fibrotic stress primes KCs for the release of TXA 2 by inducing the upregulation of cytosolic phopholipase A 2 (cPLA 2 ), COX-2, and thromboxane synthase (TS) (10), the three key enzymes for its biosynthesis (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…2 The morphological and molecular changes that the cirrhotic liver undergoes form the basis for subsequent alterations in the generation, degradation, and the response to vasodilators and vasoconstrictors. Hepatic vascular tone rearrangements originate from an increase in the levels of vasoconstrictors, such as thromboxane (TX) A 2 [3][4][5][6] or cysteinyl leukotrienes (Cys-LTs, leukotrienes C 4 , D 4 , E 4 ), 7,8 and a decrease in the levels of vasodilators. [9][10][11][12][13] One mechanism in addition to the many others for the intrahepatic hyperresponsiveness to vasoconstrictors in the cirrhotic liver is the up-regulation of Rho kinase-mediated contraction.…”
mentioning
confidence: 99%